(untitled) (Journal of Oriental Studies, 2026)
Hong Beom-do has been considered a legendary hero of the Korean independence movement, but few records remain about him, leaving open the question of why he became a member of the Russian Revolutionary Army. In South Korean society, his ideological legacy is at the center of historical debates surrounding his political ideology: some define him as a hero of the independence movement, others as a communist collaborator. This study sheds light on Hong’s independence struggle and his ideological journey as reflected in Korean literature Historical novel Hong Beom-do. The novel based on Hong’s battle diary and the memoirs of his veteran comrades, was written by former Soviet Korean writer Kim Se-il during the late Soviet period. In conclusion, Hong was attracted by the communist ideology of equality for all and the advanced Russian weaponry, and he accepted Lenin’s support and joined the Russian Revolutionary Army when the Korean Independence Army was on the verge of disbandment in the northern border area of the Korean Peninsula. But above all, the decisive reason he went to Russia was that he judged it to be the only way to continue the struggle for national independence in the complex and dynamic international political changes in the Far East at the time. The results of this study on Hong’s ideological journey through collective memory will provide an important clue to alleviating the debate and conflict over the history of the Korean independence movement. Keywords: Hong Beom-do, Korean Independence Struggle, Ideological journey, Soviet historical novel, historical memory.